2016
DOI: 10.1007/978-3-319-49622-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Abstracted Extremity Representation for Automatic Fugl-Meyer Assessment

Abstract: Summary. Given its virtually algorithmic process, the Fugl-Meyer Assessment (FMA) of motor recovery is prone to automatization reducing subjectivity, alleviating therapists' burden and collaterally reducing costs. Several attempts have been recently reported to achieve such automatization of the FMA. However, a cost-effective solution matching expert criteria is still unfulfilled, perhaps because these attempts are sensor-specific representation of the limb or have thus far rely on a trial and error strategy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The raw signals vary between the sensors and are not a good representation for classification purposes [28]. An abstract representation is obtained by transforming data to a common space as we have previously reported [22], [23].…”
Section: A Abstract Data Representation Common To Multiple Sensing Gmentioning
confidence: 99%
“…The raw signals vary between the sensors and are not a good representation for classification purposes [28]. An abstract representation is obtained by transforming data to a common space as we have previously reported [22], [23].…”
Section: A Abstract Data Representation Common To Multiple Sensing Gmentioning
confidence: 99%
“…Angelica g. Thompson Butel et al employed three methods to assess limb function improvement in stroke patients and concluded that FMA is also appropriate for individuals with low motor function [4]. Patrick Heyer and Seunghee Lee utilized sensors for the research and development of full-automatic evaluation of FMA in their research on FMA automation applications at home and abroad [5][6]. Edwin Daniel Oña, E. D. used SPARC to measure the motion smoothness [7].…”
Section: Introductionmentioning
confidence: 99%